Analysis of Molecular Docking and Dynamics Simulation of Mahogany (Swietenia macrophylla King) Compounds Against the PLpro Enzyme SARS-COV-2 - Lalu Sanik Wahyu Fadil Amrulloh; Nuraini Harmastuti; Andri Prasetiyo; Rina Herowati (Universitas Airlangga, 2023)
Background: Using natural ingredients as antivirals can be considered a treatment for SARS-CoV-2. One of the potential plants, mahogany (Swietenia macrophylla King), is widely used in various countries as an antiviral treatment. Paparin-like protease (PLpro) is an essential cysteine